REVISION SISTEMATICA, ANALISIS CLADISTICO Y BIOGEOGRAFIA HISTORICA DE LOS GENEROS FALKLANDIUS ENDERLEIN Y LANTERIELLA GEN. NOV. (COLEOPTERA: CURCULIONIDAE) (Acta Entomológica Chilena, 2022)
The gcnus Falklandius Enderlein (Curculionidae: Rhytirrhininae: Listroderini) comprises fivespecies (3 ncw described in this contribution) inhabiting the Falkland Islands, Tierra del Fuego, andMagallanes. The genus is redescribed, descriptions and illustrations of its species are presented, anda key for their identificalion is provided. The genus Lanteriella, most closely related to Falklandius,is described for the endogean species L. microphtalma spec. nov. A cladislic analysis of the speciesof Falklandius is perforined, using 27 characters from external morphology, body vestiture and maleand female genitalia. In the most parsimonious cladogram, of 33 steps and a consistency Índex of0.68, the species follow the sequence F. antárcticas (Stierlin), F. turbificatus Enderlein, F. goliathspec. nov., F. kitscheli spec. nov., and F. magellanicus spec. nov. A panbiogeographic analysis isapplied to Falklandius and other animal and plant taxa (totalyzing 50) distributed in the FalklandIslands, Tierra del Fuego, Magallanes, and various subantarctic islands. This analysis establishes thatdifferent generalized tracks overlap in the Falkland Islands and Tierra del Fuego, identifying theseareas as nodes.